Analysis of Financial Ratio Before and During Covid-19 in Consumer Goods Industry Sector 2018-2021 - Sindik Widati; Edi Tri Wibowo; Adibah Yahya; Nur Safa’ah (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study aims to analyze whether there are differences in Liquidity, Profitability, Solvency, Activity and Market Ratios between before and during the Covid-19 pandemic in Manufacturing Companies listed on the Indonesia Stock Exchange in the consumer goods industry sector in 2018-2021. The financial ratios used are Current Ratio, Debt to Equity Ratio, Gross Profit Margin, Total Assets Turnover, and Price Earnings Ratio. The samples were 43 companies using purposive sampling method for sampling. The type of data in this study is secondary data and data collection methods with documentation obtained from financial reports sourced from the Indonesia Stock Exchange. Data analysis techniques used descriptive statistical tests, normality tests, and hypothesis testing with the Paired Sample t-Test which was supported by the Wilcoxon Signed Rank Test. Data analysis using the Descriptive Statistical Test shows a decline in financial performance in 2020-2021 as a result of the co-19 pandemic. The results of the different tests in this study show that there are differences in the Debt to Equity Ratio and Gross Profit Margin. This is because the average income has decreased compared to before the Covid-19 pandemic, and companies cannot control their production costs and debts effectively. While the ratio of Current Ratio, Total Assets Turnover and Price Earnings Ratio there is no difference. The company is able to manage its assets quite well and can stabilize its share price.